Relationship of obesity and physical activity among primary students aged 7 to 12 years old in urban of Pejabat Pendidikan Daerah (PPD) Gombak / Aleena Myra Rosli - Rosli, Aleena Myra (Faculty of Sports Science and Recreation, 2018)
Childhood obesity is related to sedentary lifestyle and many other factors. Hence, the aim of this study is to determine the relationship of obesity and physical activity among primary students aged 7 to 12 years old in urban area of Pejabat Pendidikan Daerah (PPD) Gombak. This study includes five different schools which are Sk Taman Setia, Sk Taman Melawati 1, Sk Taman Melawati 2, Sk Taman Permata and Sk Keramat (N=250) aged among 7 to 12 years old divided into gender which male is one hundred and thirty-three (N=133) and female is one hundred and seventeen (N=117) are participated in this study. A measurement of height (m) and weight (kg), International Physical Activity Questionnaire (IPAQ) were used in this study. The findings from this study shows that male higher iii obesity (31.37±1.42) compare to female (30.62±1.45). Other than that, male tends to be more physically active (1640.99 ± 480.93) than female (1608.66 ± 545.91). There is large negative correlation on relationship of body mass index and physical activity. As a conclusion, children should spend some time in doing physical activity at least 60 minutes per day in order to avoid the risk of obesity.